2019
DOI: 10.1017/jfm.2018.952
|View full text |Cite
|
Sign up to set email alerts
|

Droplet levitation over a moving wall with a steady air film

Abstract: In isothermal non-coalescence behaviours of a droplet against a wall, an air film of micrometre thickness plays a crucial role. We experimentally study this phenomenon by letting a droplet levitate over a moving glass wall. The three-dimensional shape of the air film is measured using an interferometric method. The mean curvature distribution of the deformed free surface and the distributions of the lubrication pressure are derived from the experimental measurements. We vary experimental parameters, namely wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“…According to the predictions, the film thickness increases with the air film velocity at a larger rate for small drops. Sawaguchi et al (2019), in similar measurements, found that the thickness of the air film was evenly distributed at the bottom of low viscosity drops, while large oscillations were observed for high viscosity drops. Sreenivas et al (1999) who studied the levitation of drops at a hydraulic jump suggested that the force needed to balance the weight of the drop was W = f L µ a vL y L 2…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…According to the predictions, the film thickness increases with the air film velocity at a larger rate for small drops. Sawaguchi et al (2019), in similar measurements, found that the thickness of the air film was evenly distributed at the bottom of low viscosity drops, while large oscillations were observed for high viscosity drops. Sreenivas et al (1999) who studied the levitation of drops at a hydraulic jump suggested that the force needed to balance the weight of the drop was W = f L µ a vL y L 2…”
Section: Introductionmentioning
confidence: 59%
“…It was, however, shown that the drops do not always stay at the hydraulic jump steadily but oscillate (Pirat et al 2010), which is not conducive to the study of the dynamics of the trapped film. Similarly, steady drop floating was achieved by releasing drops on the inner surface of a rotating cylinder coated with a thin layer of the same liquid as in the drop (Davis et al 1980;Thoroddsen & Mahadevan 1997;Lhuissier et al 2013;Sawaguchi et al 2019). Whether the drops can levitate on the surface or not depends a lot on the impact conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For a spherical two-particle system, the lubrication forces have been well described in the Stokes regime [12][13][14][15][16]. On the other hand, more general lubrication between objects of nonspherical geometries may be described by a small deformation approximation [17], the Benny-Lin equation for small perturbation in film flow on an inclined plane [18,19], or by the Reynolds lubrication equation [20] which shows that the pressure is independent of the wall-normal direction even for deformable particles such as biological cells [21,22] and bubbles or droplets [23]. Figure 1 shows a two-dimensional schematic of a narrow gap between two moving solid surfaces.…”
Section: Introductionmentioning
confidence: 99%